2021
DOI: 10.31703/gssr.2021(vi-ii).07
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advertising Appeals on Children's Well-being: Exploring the Moderating Role of Disposition

Abstract: This research study aimed to examine the effect of advertisement appeals on the psychological well-being of children and assess the moderating role of disposition in the relationship of children's psychological well-being and advertisement appeals. The study was conducted by using primary data. Data was collected through the survey conducted in three-time lags from the children of age ranging from 8 to 12 years. A self-administered questionnaire was distributed among a sample of 578 children. For the selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(66 reference statements)
1
1
0
Order By: Relevance
“…This indicated that the higher the level of emotional intelligence among individuals, the better the psychological well-being of the individual. This is consistent with a study conducted by Mehmood and Gulzar et. al (2014), on the relationship of emotional intelligence to adolescent psychological well-being, who found a significant positive relationship between emotional intelligence variables and psychological well-being.…”
Section: Introduction and Literature Reviewsupporting
confidence: 94%
“…This indicated that the higher the level of emotional intelligence among individuals, the better the psychological well-being of the individual. This is consistent with a study conducted by Mehmood and Gulzar et. al (2014), on the relationship of emotional intelligence to adolescent psychological well-being, who found a significant positive relationship between emotional intelligence variables and psychological well-being.…”
Section: Introduction and Literature Reviewsupporting
confidence: 94%
“…Children's insights about the brands, purchase intention and request to their parents for purchase are significantly influenced by attractive advertisement messages (Mehmood, 2021); Van Reijmersdal, Rozendaal, ESmink, Noort and Buijzen, 2017.) Therefore, it is obvious that the positive attitude towards the product's advertisement leads to like the product (Mortimer, 2008).…”
Section: Advertising Appeals and Children Commercialsmentioning
confidence: 99%